Current approaches and problems faced by orthopedic surgeons in all-inside arthroscopic meniscus repairs (Annals of Medical Research, 2023)
Aim: All-inside meniscal sutures are frequently the treatment of choice in arthroscopic practice. However, the literature contains limited evidence of the technical issues experienced during the procedure. We aimed to evaluate the technical difficulties encountered during the placement of all-inside meniscal repair sutures according to the surgeon’s experience and the success rate of the suture placement.Materials and Methods:  We invited orthopedic surgeons across the country to complete a questionnaire through an online platform. Participants were asked ten questions about their demographic information, general surgical approach to meniscal tears, and experience with intraoperative complications specific to all inside meniscus sutures.Results: A total of 100 orthopedic surgeons participated in our study. Of these, 37% had been working as an orthopedic surgeon for more than ten years. Twenty-five per cent performed more than two arthroscopic knee surgeries per week. Fifty-six per cent of the surgeons were protective for the displaced red-white zone meniscal tears. Although 90% of the participants stated that the technique was more effortless, only 12% thought the clinical results were better than the other techniques. More than 50% of the participants indicated that they had difficulty when placing the sutures successfully. The most common problem was the inability to fix the meniscus sufficiently and the deformation of the instruments inside the joint. When we compared the complications according to the surgeon's experience, even among the surgeons who performed more than 100 arthroscopic surgeries per year, 34% had trouble applying these sutures successfully.Conclusions: Although all-inside meniscus sutures are generally believed to decrease the operative time and be technically more straightforward, even the most experienced surgeons have difficulty applying these sutures, and the reliability of these sutures is low.